A critical review of separation technologies in lignocellulosic biomass conversion to liquid transportation fuels production processes. Issue 4 (3rd April 2022) - Ibarra-Gonzalez, Paola; Christensen, Lars Porskjaer; Rong, Ben-Guang
Abstract: A critical review of separation methods and technologies for lignocellulosic biomass conversion through thermochemical processes to liquid fuels is presented. The multistep processing of biomass includes thermochemical conversion, product upgrading and final fuels separation. Chemicals and biofuels are produced from intermediate streams in each processing section. In the thermochemical conversion, product streams from gasification, liquefaction and pyrolysis require separation technologies for conditioning of main products and removal of impurities. In the upgrading, the separation technologies play an important role in the definition of different process configurations for conversion of unstable hydrocarbon fractions into specific biofuel types and chemicals via upgrading reactions. In the final fuels' separation section, separation technologies must be implemented to separate desired biofuels from gases, chemicals, wastewater and solid products. Hence, for total biomass to liquid (BtL) processes, separation technologies are important to improve the interface between the sections and to determine the substructures and subsequent processing methods and techniques. It is observed that separation is more demanding in such biorefinery processes for BtL productions. On the other hand, the widely used separation methods in refineries are also mostly employed in BtL processes including phase separation, scrubbing, filtration, extraction, absorption, distillation, fractionation.